First steps into lean at the Australian Red Cross Blood Service. (June 2016) - Jones, T. R.; Wilkie, G.
Abstract : Aim: The drivers for introducing lean principles to the Blood Service were as follows: Pressure on the health dollar and a commitment to providing value for taxpayer funding; Recognition of process inefficiencies including comparative international benchmarking Method: In early 2013, the Manufacturing Division of the Blood Service launched a series of kaizen or rapid improvement events. Around thirty front‐line staff and supervisors were trained in the tools and techniques and encouraged to address some long‐standing improvement opportunities. Results: Lean awareness programmes were developed and rolled out to all manufacturing employees, and this was built into the induction programme for new employees. Visual management, short interval production meetings and gemba walks were introduced and quickly drew attention from other parts of the Blood Service. Waste reduction, pull, flow, level production and lean production systems all feature in the new plan as key enablers to the achievement of strategic goals. Conclusion: The Blood Service is already seeing great benefits from the pursuit of a lean continuous improvement culture. While most of the gains have been within the Manufacturing Division to date, momentum is building in other parts of the business, supported by a small central team of business process improvement specialists. The changes in manufacturing have resulted in improvements in meeting customer demand and strong improvements in productivity in both processing and testing.